Modeling rubber prices as a GBM process - Ibrahim, Siti Nur Iqmal (Indian Society for Education and Environment, 2016)
This paper shows that the prices of rubber type SMR and type centrifuged latex can be modeled as a geometric Brownian motion process. A numerical simulation of the prices of the rubbers is given to illustrate the approach.